FEATURES OF CORROSION ACTIVITY OF MICROBIAL COMMUNITIES OF GAS-PIPELINE FERROSPHERE LAID IN SANDY SOIL - Н. Р. Демченко; I. М. Курмакова; О. П. Третяк (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Aim. To study the sulfidogenic microbial communities road gas-pipeline ferrospheres laid in the sandy soil and the determination of its composition was the aim of this research work. Methods. The method of limiting dilution (plating cell suspension to appropriate liquid selection medium) was used for detection and isolation of the components of communities of bacteria and microscopic fungi complex. Due to quantitative and qualitative composition, sulfidogenic community of ferrospheres in corrosive dangerous. Pure cultures of sulfate-reducing bacteria were obtained by planting numerous individual colonies on solid and liquid medium Postgate «B». Results. The dominant strain of sulfate-reducing bacteria – М-4.1 described by morphological and cultural characteristics has been isolated and identified by using PCR, with the use of universal primers to the fragments of 16S rRNA genes. When conducting a comparative analysis of DNA sequencer which encodes 16S rRNA gene of tested bacteria with the strains of similar sequences from the GenBank database, sulfate reducing bacteria strain M-4.1 belonging to Desulfovibrio genus has been confirmed. Microfungi were isolated by planting soil suspension dilutions with agar Czapek-Dox in Petri dishes. Fungal identification was carried out on the basis of their morphological and cultural features using determinants. 78 microfungi cultures belonging to Anamorphic fungi group (12 species of 5 genera), have been isolated. Conclusions. Thus, this scientific study has shown that in the ferrospheres on the surface of damaged road gas-pipeline laid in the sandy soil the corrosion dangerous abundance and species composition of complex physiological bacteria group and micromycetes is formed.